Intraoral Repair of All Ceramic Fixed Partial Denture Utilizing Preimpregnated Fiber Reinforced Composite - Turkaslan, Süha; Tezvergil-Mutluay, Arzu (European Journal of Dentistry, 2008)
All ceramic fixed partial dentures (FPD)s exhibit enhanced biocompatibility and esthetics as compared to metal-ceramic restorations. However, framework fractures are frequently reported especially when the connector dimensions are inadequate to withstand the high tensile stresses. The repair of the failed connector would be desirable rather than the complete removal and renewal since the latter is an expensive and time consuming procedure. Furthermore, the replacement or removal of the restoration for extra-oral repair purposes might increase the risk of destroying the entire restoration or damaging the abutment teeth during the removal. This article presents a direct intra-oral method that may be used to repair the connector fractures of all-ceramic FPDs which are otherwise clinically satisfactory. In the present technique, the connector is reconstructed intraorally utilizing composite resin restorative material reinforced with E-glass-fiber. (Eur J Dent 2008;2:63-68)
Keywords: Fixed partial denture; All-ceramic; Fiber-reinforced composite; Intra-oral repair; Fracture